GOOD GOVERNANCE DALAM RELOKASI PASAR SELODANG KELAPA DI KABUPATEN INDRAGIRI HILIR - Hikmatyas Hikmatyas; Mimin Sundari Nasution (Public Service and Governance Journal, 2023)
Selodang Kelapa Market was previously known as the Floating market because it was built on the Indragiri river in the Tembilahan District of the city, over time, the market building has begun to run out of age, some parts of the market were damaged and part of the market floor collapsed making the Indragiri Hilir Government immediately relocate market traders by building temporary shelters (TPS). The purpose of this study is to determine the application of Good governance in the relocation of the Coconut Selodang Market in Indragiri Hilir Regency and the inhibiting factors of the implementation of Good governance in the relocation of the Coconut Selodang Market in Indragiri Hilir Regency. This research uses the theory of Good Governance Characteristics according to UNDP in Mardiasmo (2004) there are seven indicators, namely Participation, transparency, responsiveness, justice, effective and efficient, accountable, and the rule of law. This type of research is descriptive qualitative research. The collection of necessary data, both primary and secondary data, is collected through interviews, observations, documentation, then analyzed so that conclusions can be drawn. The result of this study is that the principles of Good Governance in the relocation of the Coconut Selodang Market in Indragiri Hilir Regency have not been implemented properly, as for the constraints, namely budget constraints, lack of awareness of traders and the location of development.